The Role of Content Creators on Sharia Stock Investment Decisions in Gen-Z Mediated by Digital Financial Literacy - Muhammad Agus Irawan; Bayu Tri Cahya (Universitas Negeri Padang, 2025)
This study aims to examine the effect of the role of content creators on sharia stock investment decisions in generation-Z, with financial literacy as a mediating variable. This study involved generation-Z who live in the Ex-Karesidenan Pati area, which includes Pati, Rembang, Blora, Jepara, and Kudus regencies. The data collection process uses a questionnaire and data analysis techniques using the SmartPLS3 application. The research findings show that the role of content creators has a direct correlation with sharia stock investment decisions, the role of content creators has a significant positive effect on digital financial literacy, digital financial literacy has a significant positive effect on sharia stock investment decisions, and the mediation variable of digital financial literacy can mediate the effect of the role of content creators on sharia stock investment decisions. This research illustrates that the existence of content creators who have content about finance and investment is a party that plays a crucial role in making investment decisions today